The Function of Baitul Maal in Public Financial Policy: A Perspective from Islamic Economics - Intan Shaferi; Rio Dhani Laksana (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Conventional economic objectives tend to focus on material gains, often neglecting